Prosthetic rehabilitation of an ocular defect with post-enucleation socket syndrome: A case report - Pokpong Amornvit; Dinesh Rokaya; Binit Shrestha; Theerathavaj Srithavaj (Elsevier, 2014)
Ocular trauma can be caused by road traffic accidents, falls, assaults, or work-related accidents. Enucleation is often indicated after ocular injury or for the treatment of intraocular tumors, severe ocular infections, and painful blind eyes. Rehabilitation of an enucleated socket without an intraocular implant or with an inappropriately sized implant can result in superior sulcus deepening, enophthalmos, ptosis, ectropion, and lower lid laxity, which are collectively known as post-enucleation socket syndrome. This clinical report describes the rehabilitation of post-enucleation socket syndrome with a modified ocular prosthesis. Modifications to the ocular prosthesis were performed to correct the ptosis, superior sulcus deepening, and enophthalmos. The rehabilitation procedure produced satisfactory results. Keywords: Ocular trauma, Enucleation, Socket syndrome, Ocular prosthesis